20-Over Versus 50-Over Cricket: Is There a Difference?. (October 2015) - Cannonier, Colin; Panda, Bibhudutta; Sarangi, Sudipta
Using 2008-2009 data, we identify winning input combinations for the game of cricket in two different formats: 50-over one-day internationals and 20-over games from Twenty20 internationals and the Indian Premier League. We find that attacking batting and bowling are the best determinants of the winning probability in both formats in an international setting despite their 30-over difference. Interestingly, attacking batting and defensive bowling are the optimal input combinations in the league version of the 20-over format. Finally, we speculate about their implications for the future of cricket, especially for the popularity of formats, choices of players, and player development.